2009
DOI: 10.1038/nature08298
|View full text |Cite
|
Sign up to set email alerts
|

The avian Z-linked gene DMRT1 is required for male sex determination in the chicken

Abstract: Sex in birds is chromosomally based, as in mammals, but the sex chromosomes are different and the mechanism of avian sex determination has been a long-standing mystery. In the chicken and all other birds, the homogametic sex is male (ZZ) and the heterogametic sex is female (ZW). Two hypotheses have been proposed for the mechanism of avian sex determination. The W (female) chromosome may carry a dominant-acting ovary determinant. Alternatively, the dosage of a Z-linked gene may mediate sex determination, two do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
618
0
22

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 755 publications
(670 citation statements)
references
References 30 publications
30
618
0
22
Order By: Relevance
“…For instance, all birds have a ZZ male:ZW female system and share the same Z chromosome, determining sex by means of dosage of a Z‐borne gene DMRT1 25. Snakes, with a different ZW pair, also appear to be very stable, at least in the two families (Colubridae and Viperidae) with highly degraded W chromosomes 26.…”
Section: How Are Sex Chromosomes Rearranged or Replaced?mentioning
confidence: 99%
“…For instance, all birds have a ZZ male:ZW female system and share the same Z chromosome, determining sex by means of dosage of a Z‐borne gene DMRT1 25. Snakes, with a different ZW pair, also appear to be very stable, at least in the two families (Colubridae and Viperidae) with highly degraded W chromosomes 26.…”
Section: How Are Sex Chromosomes Rearranged or Replaced?mentioning
confidence: 99%
“…A single, Y-linked dominant gene DMY also determines sex in the medaka fish Oryzias latipes [96] but is absent from closely related species [97], indicating recent acquisition of a novel sex-determination system. In birds, the Z-linked gene DMRT1 forms a strong candidate for dosage-dependent single-gene sex determination [98], although the possibility that DMRT1 is regulated by upstream factors cannot be excluded.…”
Section: J E Ironsidementioning
confidence: 99%
“…Several sex determination and sex chromosome-linked genes in vertebrates such as Dmy in medaka (Matsuda et al, 2002;Nanda et al, 2002), DM-W in the W chromosome of African clawed frog (Yoshimoto et al, 2008), and Dmrt1 in the Z chromosome of birds (Smith et al, 2009), have been shown to be recently duplicated homologs of Dmrt1. Because of the high evolutionary conservation and the newly recruited role in vertebrates (Herpin and Schartl, 2011;Xia et al, 2007), Dmrt1 also allows us to analyze the evolutionary history of genome duplication through examination of divergence and phylogeny of the duplicated genes.…”
Section: Introductionmentioning
confidence: 99%